2011
DOI: 10.1111/j.2042-3292.2011.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Welfare issues related to transport and handling of both trained and unhandled horses and ponies

Abstract: Summary Dehydration and increased risk of respiratory problems are common outcomes of transport, and both appear to be related to journey duration, emotional effects, such as fear, and challenging environmental conditions. Welfare may be improved by familiarising equines with transport vehicles and loading procedures before travel starts, and by providing thermally comfortable and well ventilated conditions during the journey. For long road journeys, rest breaks with drinking water should be given. Both traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 38 publications
2
51
0
Order By: Relevance
“…These findings support the assertions commonly found in the literature that horses should be managed during loading and travelling by experienced and educated people [13, 34, 35]. Our finding may be linked not only with limited experience in horse handling but also in driving skills.…”
Section: Discussionsupporting
confidence: 92%
“…These findings support the assertions commonly found in the literature that horses should be managed during loading and travelling by experienced and educated people [13, 34, 35]. Our finding may be linked not only with limited experience in horse handling but also in driving skills.…”
Section: Discussionsupporting
confidence: 92%
“…Although the transport of horses is a common practice, the first transport event will always be a novel stressful stimuli [9], which could increase stress if performed closely to weaning. Results showed that cortisol was significantly greater after transport (T-A, Table 1) (P ¼ .001).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of transport right after weaning has been studied in other species such as lambs [7] and calves [8]; however, there is scarce literature available on the transport of foals. Weeks et al [9] state that it is inappropriate to wean foals at the time of transport because the stress of transport can compound the social distress of weaning. Weaning is a stressful event that can cause behavioral and physiological disruption [10].…”
Section: Introductionmentioning
confidence: 99%
“…Tamed horses travel in single stalls within the vehicle, whereas unhandled 144 horses are more inclined to be transported in groups. It is common for mares to travel loose with their 145 foal within a box inside the truck (Weeks et al, 2012). 146…”
Section: Transportation Toward a New Stall 141mentioning
confidence: 99%
“…During 349 a 24 hour trip, a stop is needed at least every 4 hours to provide the horse with the opportunity to 350 urinate; horses urinate approximately six times daily and male horses in particular need to be able to 351 stand in a particular posture which is difficult to do comfortably en route (Weeks et al, 2012) . 352…”
Section: Effect Of Fasting and Water Intake 328mentioning
confidence: 99%